Resilience can Predict the Increase in the Influence of Job Satisfaction on each Individual's Work Performance - Singarimbun, Selly Marcelina; Hasanuddin, Hasanuddin; Hardjo, Suryani (Yayasan Ilomata, 2025)
Employee work performance looks different even though they admit that they have the same job satisfaction, so the research questions to be asked are, is there a direct effect of job satisfaction on job performance? and is there an indirect effect of job satisfaction on job performance through resilience?. So far, it is known that job satisfaction is an important factor, but it does not measure the resilience that occurs in individuals, even though sustainable work performance occurs not only because they are satisfied with their jobs but resilience plays an important role in long-term work. This study uses a non-experimental quantitative approach with a case study approach because it aims to see a group of samples and not to generalize the results of the study. Samples were collected by being selected based on job performance assessments from the research location. Data were taken using three scales and analyzed with mediation. The results of this study explain that rejecting the first null hypothesis, which means that there is a direct effect of job satisfaction on job performance significantly. Then rejecting the second null hypothesis, which means that there is an indirect effect of job satisfaction on job performance through resilience significantly. The conclusions and suggestions in this study are explained further.